Bystander CPR in two Pittsburgh communities - Kathleen Winter (Universidad de Alicante, 2012)
Despite recent reduction in mortality, coronary heart disease (CHD) continues to be the leading cause of death in the United States. Most of these deaths occur suddenly and out-of hospital. There is strong evidence that cardiopulmonary resuscitation (CPR) provided by a bystander at the scene of an arrest doubles the chances of survival for a victim. It is clear that the death rate for coronary heart disease is higher among blacks than among whites, yet black individuals are less likely to receive bystander CPR. Research evidence as to exactly why this problem exists is not clear (Cowie, et al., 1993). This study proposes to refine and test a questionnaire which will identify the number of individuals trained to do CPR, their willingness to perform CPR, and potential barriers to performance. This will then be administered to a random sampling of adults residing in two Pittsburgh communities where demographics indicate a high proportion of black residents. Based on the data, the investigators will seek external funding to develop a culturally competent provide CPR education and remove barriers willingness to perform CPR for members of intervention that will impacting on the two communities.